(untitled) (Research, Society and Development, 2020)
The purpose of this article is to present a study on the critical work of Kant’s practice. A theoretical essay is made in which it seeks to unveil Kantian knowledge. Among the three famous critical exposures by Immanuel Kant (1724-1804), the Critique of Practical Reason (1788) is generally pointed out as the great moral project of the Königsberg philosopher. In the first criticism, namely, the Critique of Pure Reason (1781), speculative thinking was indicated as a kind of prolegomenon for a reflection on the autonomy of the practical scope of reason. Kant wrote the second Critique in a controversial environment, in which the Foundations of Metaphysics of Customs (1785), which serves as an introduction to the main themes of his second Critique, had suffered several attacks from his contemporaries due to their alleged abstract formulations. Thus, the Critique of Practical Reason arose motivated by the questions posed against the Foundations, however, despite having this critical environment around him, Kant did not limit that to a merely polemical work and continued his project of founding a metaphysics of morals . If, on the one hand, such a project contributed to the rejection of the mistakes of its most staunch critics, on the other, and more importantly, it wished to demonstrate the universality of rational unity that precedes virtuous human action.